2022
DOI: 10.3390/molecules27030678
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Large-Scale HSCCC Separation and Neuroprotective Effects of Polyphenols from Moringa oleifera Leaves

Abstract: Moringa oleifera leaves have been widely used for the treatment of inflammation, diabetes, high blood pressure, and other diseases, due to being rich in polyphenols. The main objective of this work was to largely separate the main polyphenols from Moringa oleifera leaves using the technique of high-speed counter-current chromatography (HSCCC). The phenolic composition in Moringa oleifera leaves was first analyzed qualitatively and quantitatively by UPLC-Q-Exactive Orbitrap/MS and UPLC-QqQ/MS, respectively, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Various factors were analyzed, including the rotation speed and the flow rate of the mobile phase. The flow rate of the mobile phase directly affects the amount of stationary phase fixed in the column, separation time, and peak resolution [ 29 , 32 ]. In this study, the effect of solvent systems at rotation speeds of 800 rpm/min, 900 rpm/min, and 1000 rpm/min on the retention of the target compound's stationary phase was investigated by comparing the retention of AA, QCN, and KPL in HSCCC.…”
Section: Resultsmentioning
confidence: 99%
“…Various factors were analyzed, including the rotation speed and the flow rate of the mobile phase. The flow rate of the mobile phase directly affects the amount of stationary phase fixed in the column, separation time, and peak resolution [ 29 , 32 ]. In this study, the effect of solvent systems at rotation speeds of 800 rpm/min, 900 rpm/min, and 1000 rpm/min on the retention of the target compound's stationary phase was investigated by comparing the retention of AA, QCN, and KPL in HSCCC.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin is among the abundant flavonoids of M. oleifera (Vergara-jimenez, Almatrafi, & Fernandez, 2017). The leaves contain the highest quercetin, among other flavonoid compounds with four of the quercetin derivatives made up the majority of the flavonoids (Coppin et al, 2013;Zhu et al, 2020;Gao et al, 2022). Moreover, Makita et al (2016) and Lin et al (2018) have revealed that the quercetin present is in significant amounts as glycosides associated with a variety of sugar moieties.…”
Section: Quercetinmentioning
confidence: 99%
“…The neuroprotective activities of astragalin are associated with the free radical scavenging ability and oxidative stress-induced influences on the brain neuronal cells ( Wasik and Antkiewicz-Michaluk, 2017 ; Riaz et al, 2018 ). Astragalin and isoquercitrin isolated from M. oleifera leaves showed potent anti-oxidative effects as enhanced cell viabilities were observed in H2O2-induced oxidative stress in PC-12 cells ( Gao et al, 2022 ). Although the associated active substances involved in the mechanism were not described, the study has found that the rate of survival for the damaged cells improved as the treatment concentration of isolated compounds increased, suggesting the effect of anti-oxidative activities.…”
Section: Neuroprotective and Anti-neuroinflammatory Effects Of ...mentioning
confidence: 99%
“…Moringa can be used as a potent neuro-protectant by reducing the formation of ROS, thereby protecting the brain (Kirisattayakul et al, 2013). The isolated polyphenols and phenolic extract from moringa leaves have demonstrated strong neuroprotective activities against H2O2-induced oxidative stress in PC-12 cells (Gao et al, 2022). A cardioprotective alkaloid ( L-N,αrhamnopyranosyl vincosamide (VR), isolated from the leaves of markedly reduced isoproterenol (ISO)-M. oleifera, induced increase in the levels of serum cardiac markers (troponin-T, creatine kinase-MB, lactate dehydrogenase and glutamate pyruvate transaminase as well as cardiac lipid peroxidation) with a parallel increase in the antioxidants suggesting its cardio-protective and free radical scavenging potential (Panda et al, 2013).…”
Section: Neuro-protective and Cardio-protective Activitiesmentioning
confidence: 99%